A Perspective Active Users Gadjah Mada University (UGM) Website Archives on Information Availability and Services - Prakoso, Ario Adi; Hanifa, Zahira (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
Background of the study: This study discusses how a user perspective to the website of the Archives of Gadjah Mada University (UGM). Focusing on UGM students who actively use the services and service UGM Archives Agency website.Purpose: So that information is available in the library and archives can be reached by information seekers, the library / archives should be able to take advantage of their nature, either by setting up a website to allow users to search for information and can be accessed anywhere.Method: The method used in this research is qualitative descriptive Supported by the theory of methods PIECES, The technique of collecting data and information used by the researchers that conduct depth interviews with informants.Findings: The results of this study indicate that, overall layout and interface of the website of the Archives of UGM has been very good and the navigation system is very easy to understand, but accessing the collection of information alone users simply find it difficult, because they have to follow the procedures are quite complicated and have to wait for the information they need.Conclusion: If users need information and want to be accessible, then the user must come directly to the UGM Archives Agency.